Analisis Persepsi Guru Terhadap Pembelajaran Berdiferensiasi dan Keterampilan Berbahasa di sekolah Dasar - Hafid, Abd; Rosmalah, Rosmalah; Satriani, DH, Satriani, DH (Universitas Negeri Makassar, 2025)
This qualitative study aims to describe teachers’ perceptions of differentiated instruction and language skills learning at SD Inpres 12/79 Biru II, Bone Regency. The findings indicate that most teachers have participated in training on differentiated instruction and understand its theoretical concepts (content, process, and product) as outlined in the Merdeka Curriculum; however, they have not yet implemented them in classroom practice. In contrast, teachers have already applied language skills learning—even though they lack a theoretical understanding of the underlying concepts, including listening, speaking, reading, writing, and the integration of these skills. The study concludes that teachers possess theoretical knowledge and perceptions of differentiated instruction but have not implemented them. On the other hand, in language skills instruction, teachers have practiced it in class without sufficient theoretical understanding of the concept as a whole. Conclusion Teachers have a theoretical perception of differentiated instruction but have not applied it in teaching. And Teachers lack an understanding of language skills instruction but have implemented it without grasping its core concepts.